Effects of nonpharmacological interventions on reducing fatigue after hematopoietic stem cell transplantation - Hedayat Jafari; Yadollah Jannati; Hassan Mahmoodi Nesheli; Somayeh Hassanpour (Journal of Research in Medical Sciences, 2017)
Fatigue is one of the main complaints of patients undergoing allogeneic and autologous hematopoietic stem cell transplantation (HSCT). Since nonpharmacological interventions are cost-effective and causes fewer complications, this study aimed to review the studies performed on the effects of nonpharmacological interventions on fatigue in patients undergoing HSCT during September 2016. MEDLINE, CINAHL, Scientific Information Database, IranMedex, PubMed, ScienceDirect, Scopus, Magiran, and IRANDOC databases were searched using Persian and English keywords. A total of 1217 articles were retrieved, 21 of which were used in this study. Exercise is known as an effective intervention in alleviating physical and mental problems of patients undergoing stem cell transplant. This review-based study showed that nonpharmacological methods such as exercise might be effective in decreasing fatigue in patients undergoing stem cell transplant. There is a multitude of studies on some of the complementary and alternative therapy methods, such as music therapy, yoga, relaxation, and therapeutic massage. These studies demonstrated the positive effects of the aforementioned therapies on reduction of fatigue in patients undergoing stem cell transplantation. All the investigated methods in this study were nonaggressive, safe, and cost-effective and could be used along with common treatments or even as an alternative for pharmacological treatments for the reduction, or elimination of fatigue in patients undergoing stem cell transplantation. Given the advantages of complementary and alternative medicine, conducting further studies on this issue is recommended to reduce fatigue in patients after stem cell transplantation.